Chromatin organization as a possible factor in the control of susceptibility to radiation-induced AML in mice - Maranon, David Gustavo, author; Bedford, Joel S., advisor; Bailey, Susan M., committee member; Weil, Michael M., committee member; Carlson, Jonathan O., committee member (Colorado State University. Libraries, 2010)
To view the abstract, please see the full text of the document.